Incentives for Research, Development, and Innovation in Pharmaceuticals - Garcia-Fontes, Walter A. (Series economia de la salud y gestion sanitaria, 2011)
Incentives for innovation are particularly relevant in the pharmaceutical industry where not all social needs provide equally profitable opportunities and where most OECD countries try to implement diffe - rent measures that promote research in these less profitable areas. The lack of incentives for innovation is especially dramatic when we take into account diseases affecting mostly low-income countries, and also diseases affecting small groups of patients. How can incentives be provided to deal with these less profitable acti - vities when no clear markets exist for the innovations being introduced? Some of the contributions of this book go into discussing alternative mechanisms to substitute for these inexistent markets, and situations where traditional instruments such as public procurement or direct subsidies have proven totally insufficient. Also, this book discusses the clear mismatch between the size of the markets being targeted and the incentives being provided.